International journal of sociotechnology and knowledge development - IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2009)
The International Journal of Sociotechnology and Knowledge Development (IJSKD) wishes to publish papers that offer a detailed analysis and discussion on sociotechnical philosophy and practices which underpin successful organizational change thus building a more promising future for today's societies and organizations. It will encourage interdisciplinary texts that discuss current practices as well as demonstrating how the advances of - and changes within - technology affect the growth of society (and vice versa). The aim of this journal is to bring together the expertise of people who have worked practically in a changing society across the world for people in the field of organizational development and technology studies including information systems development and implementation.
Also available in print.
Mode of access: World Wide Web.
Description based on: Vol. 1, no. 1 (Jan./Mar. 2009); title from title screen (IGI Global, viewed Oct. 1, 2010).
Latest issue consulted: Vol. 2, no. 3 (2010).
Keywords: Knowledge management -- Periodicals; Organization -- Information technology -- Periodicals; Organizational change -- Technological innovations -- Periodicals; Critical success factors; Culture and trust within organizations; Design and technology development issues; E-government and democracy as affected by technological change; Empowerment and team development; HRM issues for innovation and knowledge sharing; Humanistic redesign; Technological politics in organizations; Implementation issues of change and technology; Influence of human factors; Information systems development; Innovation; Knowledge management systems; Knowledge sharing; Learning organizations; Organizational change; Performance and quality of working life; Quality assessment of computer information systems; Social aspects of automation; Sociotechnical systems; Systems failures; Technological forecasting and social change; Technology in society; Using knowledge management principles; Electronic books